Nutrition Studies on Eucalyptus. IV. Diagnosis of Mineral Deficiencies in Eucalyptus globulus Seedlings - Kaul, O. N.; Srivastava, P. B. L.; Tandon, V. N. (Indian Forester, 1970)
The paper reports the symptoms on foliage and the effect on growth, branching habit and nutrient uptake caused by the deficiency of some macro-nutrients in Eucalyptus globulus seedlings. Nitrogen and potassium deficiencies produced recognisable symptoms of chlorosis and curling of leaf tips and margins respectively. There was marked effect on height growth, collar diameter and root development which were very poor in N, P and K deficiencies. This was also reflected in dry matter production.